Analisis Efisiensi Jaringan Irigasi Untuk Pertanian: Studi Kasus Desa Wangan Gede Kecamatan Tonjong Kabupaten Brebes Jawa Tengah - Putra, Dimas Ramaditya; Taufik, Muhammad; Diantoro, Wahudin (Journal of Accounting Law Communication and Technology, 2025)
The irrigation flow in the rice fields of Wangan Gede village is currently still inadequate. This is evident in several areas where there is still a shortage, and some plots have not been perfectly irrigated, and during the dry season, water needs in Wangan Gede village can be said to be insufficient. Therefore, there is a need for an efficiency analysis of the irrigation flow.The purpose of this research is to determine effective rainfall, the amount of water loss, and the efficiency of water drainage in tertiary channels. This research was conducted using the Inflow-Outflow method on tertiary channels in Wangan Gede Village, Tonjong District, Brebes Regency, Central Java. This study uses rainfall data, analysis of water flow velocity, average water flow velocity (Vav), cross-sectional area of the channel (A), inflow and outflow of water, water loss, and water drainage efficiency. Based on the analysis results, the highest reliable rainfall was found in January of period 1, amounting to 273, while the lowest was recorded from July 2019 to September 2023, amounting to 0. The average water loss in conveyance channel 1 is 0.1352 m3/s, channel 2 is 0.2398 m3/s, channel 3 is 0.2348 m3/s, channel 4 is 0.3114 m3/s, channel 5 is 0.3334 m3/s, channel 6 is 0.2360 m3/s, channel 7 is 0.1682 m3/s, and channel 8 is 0.3694 m3/s. The average efficiency for the tertiary channels is 71.240%, while the percentage of water loss in the tertiary channels is 28.760%.